Anomaly detection for elderly home care. (2nd April 2020) - ,; Nugroho, Lukito Edi; ,; Lazuardi, Lutfan; Prabuwono, Anton Satria; Pratama, Mahardhika
In this paper, we propose a model for detecting anomalies in elderly home care. Two scenarios are investigated in detecting anomalies: 1) the elderly person's vital signs and their surrounding environment; 2) the mobility patterns of the elderly. We evaluated our proposed model by employing the isolation forest which detects anomalies using an isolation approach on a random forest of decision trees. We compare isolation forest on unlabeled data with statistical methods on labelled data. Subsequently, to show the reliability of the isolation concept, we compare it with a distance measure concept. The experiment shows that isolation forest has higher detection accuracy and lower error prediction for two attributes in the first scenario: skin temperature and heart rate, whereas, in the second scenario, multi-covariance determinant has a slightly better accuracy compared to isolation forest (3.9% difference in accuracy) and has a small number of prediction errors compared to isolation forest.